Projeto de controle e implementação de piloto automático para veículos agrícolas - Sacco, Renan Rathis (2023)
This work presents the design and implementation of a steering autopilot for agricultural vehicles. Controllers are presented for the alignment and operation steps, which aims to take the vehicle to the path and keep it on it with the least possible error, respectively. Operation step controller is based on linear quadratic regulator (LQR) with output feedback, while the alignment controller uses the lookahead algorithm as the outer loop and a Linear Quadratic Tracker (LQT) with output feedback as an inner loop. Both LQR and LQT controllers use gain scheduling to ensure good performance at different operating speeds. Simulation results of the controllers with an analytical model of the vehicle are presented, which illustrate the expected results for the closed-loop system. For experimental validation of the controllers, a Massey Fergusson 6713 tractor was equipped with a GNSS receiver (Global Navigation Satellite System) with RTK correction (Real Time Kinematic), inertial sensors, an electric motor coupled to the steering and a microcontroller. The developed controllers were then implemented and experimentally tested, and the obtained results were compared to the simulation results. In experimental tests, a lateral error with a standard deviation of 2.67 cm was obtained for the operating stage and the system performance was similar for speeds between 4.3 km/h and 8.4 km/h.